1999
DOI: 10.1128/iai.67.7.3649-3652.1999
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Lesions Containing Filamentous Forms Produced by a Candida albicans Mutant That Is Defective in Filamentous Growth in Culture

Abstract: A Candida albicans efg1 cph1 double mutant is nonfilamentous under standard laboratory conditions and avirulent in mice. However, this mutant produced filaments in the tongues of immunosuppressed gnotobiotic piglets and when embedded in agar, demonstrating that an Efg1p- and Cph1p-independent pathway for promotion of filamentous growth exists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 10 publications
3
38
1
3
Order By: Relevance
“…In C. albicans and diploid S. cerevisiae ¢lamentous growth of SLAD is accompanied by invasion of the media [8,25,28]. In addition haploid S. cerevisiae strains invade rich solid media below the colonies as very short chains of cells, distinct from diploid pseudohyphae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In C. albicans and diploid S. cerevisiae ¢lamentous growth of SLAD is accompanied by invasion of the media [8,25,28]. In addition haploid S. cerevisiae strains invade rich solid media below the colonies as very short chains of cells, distinct from diploid pseudohyphae.…”
Section: Resultsmentioning
confidence: 99%
“…However, when cultured on SHAD, this C. glabrata strain invaded the agar directly below the colony as yeast cells which could not be removed by washing. recent work suggests that e¡ectors involved in processes other than ¢lamentation may play a part in this attenuation as ¢lamentous forms of this mutant were seen in infected gnotobiotic pigs [28]. The role of ¢lamentation in C. glabrata disease remains unexplored, however to our knowledge no description of C. glabrata growing in vivo as anything other than a budding yeast exists.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, the gastro-intestinal tract is colonised and the infection is disseminated within the whole body, developing oral thrush, conjunctivitis and corneal lesions and complete colonisation of the tongue [64]. It has been used for the analysis of efg1 cph1 C. albicans mutants [65]. Another murine intestinal model could also be obtained upon antibiotic treatment (1 mg ml 31 bacitracin, 2 mg ml 31 streptomycin sulfate and 0.1 mg ml 31 gentamicin sulfate) of mice orally inoculated with C. albicans.…”
Section: Strategies For Testing Putative Virulence Traitsmentioning
confidence: 99%
“…Also, the efg1v/efg1v mutant had a lower virulence when compared to the wild-type strain [140], a result that could be partially explained by a reduced ability of these mutants to cross epithelia [87]. However, a recent report from the group of Kumamoto has shown that null efg1 cph1 mutants are still able to ¢lament in vivo, produce mild thrush lesions and super¢cial lesions of the eye and colonise the tongues of immunosuppressed gnotobiotic piglets [65]. Although the model system used is not the`classical' one, these results also show the existence of Cph1p-â nd Efg1p-^independent pathways promoting hyphal formation in C. albicans [65].…”
Section: Transcription Factorsmentioning
confidence: 99%
See 1 more Smart Citation